Prostate Carcinoma: Urologist's Perspective - Murugesan, Anandan; S.M, Gowtham (Journal of Gastrointestinal and Abdominal Radiology, 2024)
Prostate cancer management has undergone radical changes in recent times, due to early diagnosis in localized stage and availability of multiple treatment modalities. But the onus of selecting appropriate treatment rests with the urologist. Radiological investigations are immensely important in these patients. Measurement of prostate-specific antigen and its derivatives is the primary investigation in the diagnosis of prostate carcinoma. Ultrasonogram is of limited utility in prostate carcinoma. Magnetic resonance imaging provides extensive information to the treating physician regarding the approach and the treatment modality to be used in the management of prostate carcinoma. Radiological investigations are the cornerstones for efficient management of prostate carcinoma.
Keywords: MRI prostate; prostate; prostate cancer; prostate imaging